Effect of Different Seed Water Content and Storage Duration towards Seed Viability of Local Genotype Brown Rice Daro Merah - Indra Dwipa; Muhsanati Muhsanati (Department of Crop Science, Faculty of Agriculture, Andalas University, 2018)
Most of rice seeds experience after ripening problem which then result in seed dormancy. This kind of dormancy could be broken through various types of treatments, including storaging in dry place for certain period. This study was aimed to evaluate the combination between seed water content and storage duration to induce the seed germination of local genotype brown rice, Daro Merah. Various levels of seed water content (6-10, 11-15, 16-20 and 21-25 %) and storage duration (2, 4, 6 and 8 weeks) were evaluated to identify its effect on Daro Merah seed germination. Data were analyzed using two-way analysis of variance where significance were further proceeded using Duncan’s New Multiple Range Test with a p>0.05. The results showed that seed germination of Daro Merah reached 95 % at five days after seeding when the seed water content was maintained at 6-10% and stored for 8 weeks. After 14 days, the germination reached 99 % and most of the seeds showed some shoots emerged from the soil. Keywords: Brown rice, germination, seed water content, storage duration, Daro Merah